Descriptive Epidemiology of Primary Biliary Cirrhosis in the Province of Quebec. (1st October 1991) - Villeneuve, Jean-Pierre; Fenyves, Daphna; Infante-Rivard, Claire
Abstract : Primary biliary cirrhosis (PBC) is a rare disease, but is usually recognized because of the characteristic clinical picture and the diagnostic specificity of antimitochondrial antibody (AMA) determination. Information on the epitlemiology of PBC is limited. The authors have examined the incidence and prevalence of PBC in the province of Quebec, where all short term hospitals are required to classify discharge summary diagnoses according to the International Classification of Diseases . Code 571.6 designates primary or secondary biliary cirrhosis. The authors reviewed the charts of all patients to whom this code was assigned during a six year period (1980-86). Two hundred and twenty-eight subjects satisfied predetermined diagnostic criteria for PBC. The mean annual incidence rate was 3.9 per 106 population, and the point prevalence in 1986 was 25.4 per 106 population. Ninety-two patients were female, with a mean age at the time of diagnosis of 55.7 years; 89.4% had positive AMA, and 10.5% were asymptomatic. As of January 1, 1989, 126 patients were alive, 91 had died, and 11 had undergone liver transplantation. Cumulative five and 10 year survivals from the time of initial diagnosis were 69% and 49%, respectively. In patients with serum bilirubins greater than 100 μmol/L (n=66), cumulative two year survival was 5.5%. These data indicate that the incidence and prevalence of PBC in Quebec arc similar to chose reported in Ontario and at the lower end of the range of chose reported in western Europe. The clinical features and evolution of PBC are also similar, and serum bilirubin is a major prognostic factor.